2021
DOI: 10.1063/5.0039221
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two dynamic power cable configurations for a floating offshore wind turbine in shallow water

Abstract: For the study of the double wave configuration for the dynamic power cable of a Floating Offshore Wind Turbine (FOWT) in shallow water, this paper presented a comparison of the hydrostatic and hydrodynamic performance between a lazy wave and a double wave configuration. The double wave shape’s parametric presentation was first developed based on an extension of a previous parametric lazy wave shape. An aero-hydro-servo-elastic integrated model fully coupling the FOWT and the dynamic power cable was then propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Fretting and wear damages to the conductors' wires, caused primarily by cyclic bending loads, have been recognized as a challenge for marine cables with metallic armor [18][19][20][21][22][23]. The current study showed that this is also challenging for marine cables without metallic armor.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Fretting and wear damages to the conductors' wires, caused primarily by cyclic bending loads, have been recognized as a challenge for marine cables with metallic armor [18][19][20][21][22][23]. The current study showed that this is also challenging for marine cables without metallic armor.…”
Section: Discussionmentioning
confidence: 65%
“…They also provide mechanical properties that reduce the risk of structural integrity degradation if appropriately designed, such as fatigue, fretting, and wear caused by cyclic loading conditions from the cable's motions. Many studies in the literature have presented results from numerical simulations and experiments of armored dynamic power cables [18][19][20][21][22][23]. Most of them emphasized bending-induced loading conditions and fatigue experiments since this loading mode causes wear and fretting damage to the cable's parts and components.…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers a new perspective on enhancing the efficiency and cost-effectiveness of cable configurations in floating offshore wind farm projects. Zhao et al (2021) conducted a study comparing two dynamic power cable configurations for floating offshore wind turbines in shallow water. Their research compared the hydrostatic and hydrodynamic performance of lazy wave and double wave configurations, utilizing a comprehensive numerical simulation approach.…”
Section: Introductionmentioning
confidence: 99%
“…The cable system serves as the conduit for transmitting electrical energy from the floating platform to the onshore location. Based on its operational conditions, the cable system can be categorized into the static cable end and dynamic cable end [9]. The former primarily refers to conventional submarine cables laid on the seafloor, while the latter is a crucial component of floating offshore wind power platforms, consisting of dynamic cables and their associated accessories [10].…”
Section: Introductionmentioning
confidence: 99%